Determination of the Summer of Bioclimatic Comfort Criteria in the Landscape Planning - Elahsadı, Amragia H Mostafa; Almansouri, Hafith Mohammed Sulayman; Bouzqayyah, Mohammed Miftah Mohammed; Çetin, Mehmet (Ondokuz Mayis Universitesi, 2024)
Bioclimatic comfort, or biocomfort, refers to the state where environmental factors such as temperature, humidity, and wind speed fall within ranges that are comfortable for human activity. This study assesses the summer bioclimatic comfort conditions in Van province, Turkey, using detailed seasonal climate data. The research analyzes the spatial distribution of key parameters, including humidity, wind speed, precipitation, and temperature, across the province during the summer season. Findings indicate that 51.37% of Van province experiences humidity levels between 40-45%, with wind speeds between 1.5-2.5 m/s in 70.12% of the area. Precipitation levels are generally low, with most of the province receiving 10-20 mm of rain. Summer temperatures range between 17-22°C, with the highest temperatures observed in the central regions. The resulting bioclimatic comfort map reveals that 99.18% of the province is suitable for biocomfort during the summer season, while only 0.82% is classified as unsuitable. These results provide valuable insights for landscape planning and urban development, particularly in creating energy-efficient and comfortable living environments.
Keywords: Bioclimatic Comfort; Climate; Landscape Planning; Summer; Biyoklimatik Konfor; İklim; Peyzaj Planlaması; Yaz; Physical Geography and Environmental Geology (Other); Fiziksel Coğrafya ve Çevre Jeolojisi (Diğer)